Teologi Jemaat GKE Damit Mengenai Eksistensi Roh-Roh Gaib di sekitar Manusia - Idrus Sasirais; Enta Malasinta Lantigimo; Ripaldi (Jurnal Teologi Pambelum, 2022)
The encounter of culture, tradition, and religion will give birth to a characteristic understanding of a particular phenomenon. There are times when everything will be balanced, but there are times when one will dominate, and the other will fade away. This research found the presence of the spirit world in the GKE Damit congregation. It was found that the influence of Javanese tradition and culture is still felt. Although not too dominant anymore, it has been mixed with the understanding of Banjarese Islam and Dayak Christianity. This phenomenon is inseparable from the fact that the majority of the followers of the GKE Damit Congregation. Most of them have Javanese cultural backgrounds, live amongst the Banjar Muslim community, and are served mainly by priests with Dayak backgrounds. This reality is very distinctive because the Javanese, Banjar, and Dayak traditions are very significant. Obedience to Christianity is precisely the most dominating, understanding that the power of Jesus Christ is above all things. They believe Jesus Christ is far more powerful than the spirits in this world.